2014
DOI: 10.1016/j.joca.2013.12.016
|View full text |Cite
|
Sign up to set email alerts
|

Primary cilia disassembly down-regulates mechanosensitive hedgehog signalling: a feedback mechanism controlling ADAMTS-5 expression in chondrocytes

Abstract: SummaryObjectiveHedgehog signalling is mediated by the primary cilium and promotes cartilage degeneration in osteoarthritis. Primary cilia are influenced by pathological stimuli and cilia length and prevalence are increased in osteoarthritic cartilage. This study aims to investigate the relationship between mechanical loading, hedgehog signalling and cilia disassembly in articular chondrocytes.MethodsPrimary bovine articular chondrocytes were subjected to cyclic tensile strain (CTS; 0.33 Hz, 10% or 20% strain)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
108
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(112 citation statements)
references
References 45 publications
3
108
0
1
Order By: Relevance
“…Mechanically induced activation of Ihh signaling in primary chondrocytes is also lost when primary cilia are absent. In articular cartilage, cilia are important for chondrocytes to respond to compression‐induced osmotic changes . Similarly, chondrocyte cilia also play a role in the growth plate's ability to sense compressive loading.…”
Section: Disrupting Primary Cilia Results In Abnormal Growth Plate Momentioning
confidence: 99%
“…Mechanically induced activation of Ihh signaling in primary chondrocytes is also lost when primary cilia are absent. In articular cartilage, cilia are important for chondrocytes to respond to compression‐induced osmotic changes . Similarly, chondrocyte cilia also play a role in the growth plate's ability to sense compressive loading.…”
Section: Disrupting Primary Cilia Results In Abnormal Growth Plate Momentioning
confidence: 99%
“…Several studies have now shown that very minor changes in cilia structure and trafficking can have dramatic effects upon functionality (Cruz et al, ; Thompson et al, ; Thompson et al, ; Tran et al, ). Thus, while the cilia disruption in +HGA cells does not influence cilia structure to the same extent as in AKU cells, it is sufficient to considerably disrupt function.…”
Section: Discussionmentioning
confidence: 99%
“…Though less is known about the transduction of mechanical load in pathologic settings, these processes appear to involve the enhancement of catabolic effectors, such as MMPs and aggrecanases [65, 66], and recent studies suggest the involvement of ciliary signaling [67] and histone modification [68]. Further mechanistic studies in the setting of injurious loading, or joint impact followed by physiologic loading, will reveal clinically relevant information for the treatment of patients following destabilizing and traumatic joint injuries.…”
Section: : Mechanical Loading At the Chondrocyte Levelmentioning
confidence: 99%